2015
DOI: 10.1016/j.bone.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Lineage tracking of mesenchymal and endothelial progenitors in BMP-induced bone formation

Abstract: To better understand the relative contributions of mesenchymal and endothelial progenitor cells to rhBMP-2 induced bone formation, we examined the distribution of lineage-labelled cells in Tie2-Cre:Ai9 and αSMA-creERT2:Col2.3-GFP:Ai9 reporter mice. Established orthopedic models of ectopic bone formation in the hind limb and spine fusion were employed. Tie2-lineage cells were found extensively in the ectopic bone and spine fusion masses, but co-staining was only seen with tartrate-resistant acid phosphatase (TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…This may be due to contribution of muscle-derived cells to chondrocytes (51,52). Notably, αSMA expression is present in some muscle cells, both myogenic satellite cells, and a separate population of stromal cells that can contribute to heterotopic bone formation (27,53). It is also possible that there is a periosteal population that is restricted to chondrogenic and perhaps fibroblastic lineages, although we are not aware of any cell populations that have shown these properties in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to contribution of muscle-derived cells to chondrocytes (51,52). Notably, αSMA expression is present in some muscle cells, both myogenic satellite cells, and a separate population of stromal cells that can contribute to heterotopic bone formation (27,53). It is also possible that there is a periosteal population that is restricted to chondrogenic and perhaps fibroblastic lineages, although we are not aware of any cell populations that have shown these properties in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kolind et al . have studied the endothelial and mesenchymal contributions to BMP2-induced bone formation using Tie2-cre and αSMA-CreERT labeled mice 21 . They found that Tie2 primarily marked endothelial cells in this model; closer evaluation of their immunostaining shows some expression of SOX9 in Tie2-labeled cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from FOP patients have suggested that both circulating cells and endothelial cells contribute to osteogenesis[16, 17]. However, studies using Cre-directed lineage tracing in murine models have indicated that hematopoietic, endothelial, and smooth muscle lineages do not contribute to bony elements within lesions formed in BMP-induced HO[1821]. In addition, myogenic lineages make little or no contribution to osteoblasts or chondrocytes in HO based on studies using Myf5-Cre and MyoD-Cre[18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, myogenic lineages make little or no contribution to osteoblasts or chondrocytes in HO based on studies using Myf5-Cre and MyoD-Cre[18, 19]. Studies with Tie2-Cre, which labels both endothelial, hematopoietic, and, in some Tie2-Cre lines, mesenchymal lineages, indicated that only the CD45 − CD31 − Sca1 + PDGFRα + population significantly contributed to bone formation[20, 21]. However, Tie2-Cre only labeled 40–50% of osteoblasts and chondrocytes in BMP-induced HO suggesting that other cell populations may be involved[19, 20].…”
Section: Introductionmentioning
confidence: 99%